Problematika Guru Dalam Mengelola Lingkungan Pembelaharan di TK Aisyiyah 18 Surabaya - Aulia Nadia Saputri; Dya Ayu Pitaloka; Haniif Mufidah; Fine Jovial Kamilia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The learning environment is one of the important factors that influences the success of the early childhood education process. A safe, comfortable and conducive learning environment can support children's optimal development, both in cognitive, language, social-emotional and physical-motor aspects. In creating a quality learning environment, teachers have an important role as facilitators and class managers who are responsible for organizing various aspects of learning to suit the needs and characteristics of children. However, in its implementation teachers often face various obstacles, such as differences in student characteristics, limited facilities and infrastructure, limited learning space, and difficulties in managing children's behavior during learning activities. This article aims to discuss the importance of the learning environment for early childhood, its impact on children's development, the importance of classroom management by teachers, as well as the problems faced by teachers in managing the learning environment at KB/TK Aisyiyah 18 Surabaya along with the strategies used to overcome them. The method used is a qualitative descriptive approach through literature studies and field observation results. The results of the discussion show that a conducive learning environment has a positive influence on the learning process and children's development. Various problems faced by teachers can be overcome through structuring the appropriate learning environment, using creative learning media, consistently applying class rules, and good cooperation between teachers and parents in supporting children's learning processes.